Sistem Pendukung Keputusan Penilaian Kinerja Pada Siswa Magang dengan Metode Simple Additive Weighting (SAW) - Nita Noptapia Sihombing; Rima Tamara Aldisa; Yudika Parulian Simatupang (Bulletin of Computer Science Research, 2024)
The apprenticeship program is a learning activity in the field that aims to introduce and develop students' skills in a real work environment. Students who will take part in internships need to prepare as well as possible, not just focusing on the academic competencies they learn at school. On the other hand, they must also have experience, knowledge, and insight into a wide world of work. So far, appraising the performance of apprentice students is primarily based on disciplinary criteria. However, there are actually several other criteria that can also be taken into consideration in assessing the performance of apprentice students, such as Discipline, Performance, Creativity, Teamwork, Adaptation and Mastery of Work Materials. To conduct a more comprehensive assessment of the performance of apprentice students, a decision support system is needed. In this study, the method used is Simple Additive Weighting (SAW). The choice of this method is due to its ability to handle assessments by considering the priority values or weights that have been assigned to each criterion. The results of this study indicate that Alternative A4, represented by "Rezka," is the best alternative with a Vi value of 0.9472.